Love Letters from Golok: A Tantric Couple in Modern Tibet, by Holly Gayley. (30th December 2018) - Galli, Lucia
Abstract : Love Letters from Golok: A Tantric Couple in Modern Tibet, by Holly Gayley. Columbia University Press, 2017. 416pp. Hb. £52.00. ISBN: 9780231180528. E-book. £52.00. ISBN: 9780231542753.